Factors Associated with Higher Sitting Time in General, Chronic Disease, and Psychologically-Distressed, Adult Populations: Findings from the 45 & Up Study - Plotnikoff, Ronald C.; Costigan, Sarah A.; Short, Camille; Grunseit, Anne; James, Erica; Johnson, Natalie; Bauman, Adrian; D’Este, Catherine; van der Ploeg, Hidde P.; Rhodes, Ryan E. (PLOS ONE, 2015)
This study examined factors associated with higher sitting time in general, chronic disease, and psychologically-distressed, adult populations (aged ≥45 years). A series of logistic regression models examined potential socio-demographic and health factors associated with higher sitting (≥6hrs/day) in adults from the 45 and Up Study (n = 227,187), including four separate subsamples for analysis comprising those who had ever had heart disease (n = 26,599), cancer (n = 36,381), diabetes (n = 19,550) or psychological distress (n = 48,334). Odds of higher sitting were significantly (p<.01) associated with a number of factors across these groups, with an effect size of ORs≥1.5 observed for the high-income ≥$70,000AUD, employed full-time and severe physical limitations demographics. Identification of key factors associated with higher sitting time in this population-based sample will assist development of broad-based, public health and targeted strategies to reduce sitting-time. In particular, those categorized as being high-income earners, full-time workers, as well as those with severe physical limitations need to be of priority, as higher sitting appears to be substantial across these groups.